The Development Of Professional Judgment Research - Claudia Wanda Melati KOROMPIS (International Journal of Environmental, Sustainability, and Social Science, 2022)
The auditor's professional judgment quality is essential to maintain and improve. Therefore, careful judgment by an independent third-party can assist the company in its operations. The purpose of this research is to see the development of judgment and decision-making (JDM) in Indonesia and its benefits in improving the quality of auditor judgment, especially auditors in the Indonesian supreme audit institution environment. This thinking is based on that (1) there has been a shift in JDM audit research from a normative model to a cognitive process (2) human cognition is limited, so a cognitive strategy is needed to assist humans in making quality judgments. This study guides designing effective empirical research using this conceptual framework. The framework adopted from this research helps improve the auditor's understanding of the appraisal process that can assist the auditor's appraisal performance by providing a practical suggestion through a cognitive strategy. The result of this research is that the personality factor is one of the factors that influence the auditor's assessment. Certain behaviors are more likely to occur if associated with high expectations and motivational reinforcement. Motivation is linearly related to individual expectations. Future researchers are expected to determine which type of character should be displayed higher. When researchers know which characters can stand out in improving performance, providing motivational reinforcement for the whole individual will be effective. Individual motivation will cause human cognition to be better because there is an urge to direct maximum thinking skills to get the best work results.